EXPERIMENTATION OF SPICES LEARNING STRATEGIES WITH THE METHOD OF PROBLEM BASED LEARNING (PBL) TO BUILD MOTIVATION AND THE ABILITY TO THINK LOGICALLY FOR VOCATIONAL SCHOOL STUDENTS - Anggita Maharani; Laelasari Laelasari (IKIP Siliwangi and I-MES, 2017)
This study aims to expose the interactions that occur in the process of mathematics learning and describe a method of learning motivation and logical mathematical thinking of students in classes. The method used in this research was a quasi-experimental design group post-test. In its implementation, this study uses a class experiment. Qualitative data are obtained in the form of motivational learning scale, whereas the quantitative data in the form of logical thinking ability score using normalized gain. The results showed the existence of a positive interaction during learning. However, learning motivation of students didn’t show a significant improvement. While the logical thinking ability of students after learning of mathematics using the strategy of SPICES with PBL method is in the category is fair. In its implementation, the strategy of SPICES needed support some teachers from several fields of science.